Treatment with the KCa3.1 inhibitor TRAM‐34 during diabetic ketoacidosis reduces inflammatory changes in the brain. Issue 5 (13th May 2016) - Glaser, Nicole; Little, Christopher; Lo, Weei; Cohen, Michael; Tancredi, Daniel; Wulff, Heike; O'Donnell, Martha
Abstract : Background: Diabetic ketoacidosis (DKA) causes brain injuries in children ranging from subtle to life‐threatening. Previous studies suggest that DKA‐related brain injury may involve both stimulation of Na‐K‐Cl cotransport and microglial activation. Other studies implicate the Na‐K‐Cl cotransporter and the Ca‐activated K channel KCa3.1 in activation of microglia and ischemia‐induced brain edema. In this study, we determined whether inhibiting cerebral Na‐K‐Cl cotransport or KCa3.1 could reduce microglial activation and decrease DKA‐related inflammatory changes in the brain. Methods: Using immunohistochemistry, we investigated cellular alterations in brain specimens from juvenile rats with DKA before, during and after insulin and saline treatment. We compared findings in rats treated with and without bumetanide (an inhibitor of Na‐K‐Cl cotransport) or the KCa3.1 inhibitor TRAM‐34. Results: Glial fibrillary acidic protein (GFAP) staining intensity was increased in the hippocampus during DKA, suggesting reactive astrogliosis. OX42 staining intensity was increased during DKA in the hippocampus, cortex and striatum, indicating microglial activation. Treatment with TRAM‐34 decreased both OX42 and GFAP intensity suggesting a decreased inflammatory response to DKA. Treatment with bumetanide did not significantly alter OX42 or GFAP intensity. Conclusions: Inhibiting KCa3.1 activity with TRAM‐34 during DKA treatment decreases microglial activation and reduces reactive astrogliosis, suggesting a decreased inflammatory response.